Knowledge, attitudes and practices of veterinarians and para-veterinarians towards antimicrobial stewardship in Malawi: underutilized strength in the fight against antimicrobial resistance - Henson Kainga; Marvin Phonera; Simegnew Adugna Kallu; Elisha Chatanga; Merning Mwenifumbo; Joseph Nkhoma; Gilson Njunga (BMC Veterinary Research)
Abstract Antimicrobial resistance (AMR) is a global public health concern, and the inappropriate use of antibiotics in animals and humans is considered a significant contributing factor. Para-veterinarians and veterinarians are vital in the fight against AMR. The study aimed to evaluate the knowledge, attitudes and practices of the para-veterinarians and veterinarians towards antimicrobial stewardship in Malawi. A cross-sectional questionnaire survey among the para-veterinarians and veterinarians was conducted from October 2024 to January 2025. A total of 69 participants, comprised of 42 para-veterinarians and 27 veterinarians, participated in this study, and the response rate for the survey was 44% (n = 158). The study used a predetermined cutoff of ≥ 55% to classify scores as having good knowledge, good practice, and a positive attitude. The study found that 85.5% of the respondents had good knowledge and 98.6% had good practices towards antimicrobial stewardship and prevention of AMR, while 92.8% had favorable attitude towards AMR and antimicrobial stewardship. The maximum obtainable scores for each construct were 11, 13 and 13 for knowledge, practice, and attitude, respectively. The overall mean scores for knowledge, practice and attitude were 11.25 ± 2.83, 8.71 ± 1.34 and 9.04 ± 1.64, respectively. These findings indicated that the respondents had good knowledge, good practices and favorable positive attitude towards AMR and antimicrobial stewardship. The study concludes that there is good level of knowledge, practice and favorable attitude among para-veterinarians and veterinarians towards antimicrobial stewardship which can be capitalized in the fight against AMR in Malawi. The veterinary professionals can be entrusted to comply with responsible antimicrobial prescriptions and use.